2020
DOI: 10.1002/ange.201916245
|View full text |Cite
|
Sign up to set email alerts
|

Fernpartizipation in Glykosylierungen von Galaktose‐Bausteinen: Direktnachweis durch kryogene Schwingungsspektroskopie

Abstract: Die stereoselektive Bildung von 1,2‐cis‐glykosidischen Bindungen ist bislang sehr anspruchsvoll. Häufig wird diese 1,2‐cis‐Selektivität durch Fernpartizipation (remote participation) von C4‐ oder C6‐Estergruppen herbeigeführt. Hierbei wird davon ausgegangen, dass ein ionisches Schlüsselintermediat, das Glykosylkation, gebildet wird. Obwohl derartige Mechanismen bereits vor Jahrzehnten postuliert wurden, konnte die exakte Struktur dieses Intermediats aufgrund seiner Kurzlebigkeit bisher nicht aufgeklärt werden.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…While all C−O bonds are destabilizing to formation of an electrophilic center at the anomeric carbon, ester‐type protecting groups tend to be more destabilizing than ether‐type groups [34–41] . Protecting groups can change the intermediate conformation through steric impedance or neighboring and remote interaction, thereby regulating the reactivity and stereoselectivity of the glycosylation reaction [42–45] . A clear relation between activation temperature, glycosyl donor reactivity, and protecting groups remains to be defined [33,46] …”
Section: Resultsmentioning
confidence: 99%
“…While all C−O bonds are destabilizing to formation of an electrophilic center at the anomeric carbon, ester‐type protecting groups tend to be more destabilizing than ether‐type groups [34–41] . Protecting groups can change the intermediate conformation through steric impedance or neighboring and remote interaction, thereby regulating the reactivity and stereoselectivity of the glycosylation reaction [42–45] . A clear relation between activation temperature, glycosyl donor reactivity, and protecting groups remains to be defined [33,46] …”
Section: Resultsmentioning
confidence: 99%
“…234,[236][237][238] An in-depth study of distal acyl groups using cryogenic infrared spectroscopy, DFT computations, and a series of systematic glycosylations, has revealed that certain ester groups can play a decisive role in shaping the stereochemical outcome of glycosylations. 234,237,238 For example, remote participation of 3-OH ester groups on mannosides is stronger than 3-OH ester groups on galactosides, while remote participation of 3-OH ester groups in glucosyl and galactosyl donors provide less assistance in guiding the stereochemical course of glycosylations. Reports on the role of 6-OH ester groups are Scheme 3 Automated glycan assembly of a library of chitin oligosaccharides.…”
Section: Influence Of Protecting Groups On the Glycosylating Agentmentioning
confidence: 99%
“…223 mixed. 144,237,238 The remote participation of 4-OH ester groups in galactose can lead to covalent bonds between the carbonyl oxygen and the anomeric carbon, to promote a-selective galactosylations. 234,238 Although the strength of remote participation requires further clarification for different types of glycosides, it offers a viable option for improving stereocontrol in glycoside synthesis.…”
Section: Influence Of Protecting Groups On the Glycosylating Agentmentioning
confidence: 99%
“…The presence of an ether at C2 such as NAP and PMB groups can also be applied to the formation of 1,2-cisglycosides through the intramolecular aglycone delivery (IAD) strategy, [34] which delivers the aglycone on the same side than the C2 tether. Long-range participating effects [35] are also possible using, for instance, the recently developed picoloyl (Pico) and picolinyl (Pic) groups. [36] These pyridine-containing groups have been shown to be of great value for the synthesis of 1,2-cis-glycosides, such as α-glucosides and β-dmannosides, [37] through a strategy pioneered by the Demchenko group and coined hydrogen-bond-mediated aglycone delivery (HAD).…”
Section: Protecting Groupsmentioning
confidence: 99%